Mesoconius Enderlein (Diptera, Micropezidae, Taeniapterinae) of Central America - Marshall, S. A. (Zootaxa, 2015)
Mesoconius Enderlein, including Zelatractodes Enderlein new synonym, is revised for Central America with one described species (Mesoconius hemithorax Frey) and five new species (M. bicolor, M. dianthus, M. nigrihumeralis, M. tigrinus, and M. zadbi). The relatively large species of this entirely Neotropical genus, most of which are restricted to narrow high elevation ranges, lack the male genital fork that characterizes all other Taeniapterinae.